Modeling the Role of Courtyards with Clusters of Buildings in Enhancing Sustainable Housing Designs - Mwfeq Al Haddad; Rami Al Shawabkeh; Mai Arar; Abdelmajeed Rjoub; Raghad Alhammad; Ahmed Senouci; Walid Maherzi (Buildings, 2024)
As urbanization increases, buildings require greater amounts of energy for heating and cooling, thereby necessitating the search for effective solutions. The courtyard is often considered a viable option; however, the limited availability and high cost of land resulting from rapid urbanization hinder its widespread use. Consequently, a courtyard with a cluster of buildings is proposed as a feasible solution to address land scarcity. Nonetheless, further investigation is required to effectively integrate this solution into neighborhood urban planning. This study examines the influence of three variables—courtyard orientation, courtyard size, and the arrangement of buildings around the courtyard—on the provision of cooling and heating for buildings. The research focuses on 216 experimental scenarios simulated using Revit software, which excels in its ability to accurately interpret input data and conduct real-time analysis depending on the variables of the building design. The results were recorded for the facades and ground, and the shaded area was computed for each scenario; following these measurements, the shadow areas on both the facade and ground were converted into percentages. The testing involved a group of buildings surrounding courtyards of four different shapes (square, rectangle, triangle, and circle). This approach aimed to identify the most efficient design for implementation in neighborhood planning contexts. The findings indicate that the shape of the courtyard significantly impacts cooling and heating of buildings. Specifically, the square courtyard is unsuitable for countries with Mediterranean climates, such as Jordan, as it can reduce shade coverage by 30%, leading to higher temperatures. Conversely, employing a rectangular courtyard results in a higher proportion of shadows compared to other shapes. The study further demonstrates the influence of the examined variables on the efficacy of the courtyard in cooling and heating of buildings.